Alcohol, tobacco and health care costs: a population-wide cohort study (n = 606 947 patients) of current drinkers based on medical and administrative health records from Catalonia. (8th January 2018) - Miquel, Laia; Rehm, Jürgen; Shield, Kevin D; Vela, Emili; Bustins, Montserrat; Segura, Lidia; Colom, Joan; Anderson, Peter; Gual, Antoni
Abstract: Background: Most cost of illness studies are based on models where information on exposure is combined with risk information from meta-analyses, and the resulting attributable fractions are applied to the number of cases. Methods: This study presents data on alcohol and tobacco use for 2011 and 2012 obtained from a routine medical practice in Catalonia of 606 947 patients, 18 years of age and older, as compared with health care costs for 2013 (all costs from the public health care system: primary health care visits, hospital admissions, laboratory and medical tests, outpatient visits to specialists, emergency department visits and pharmacy expenses). Quasi-Poisson regressions were used to assess the association between alcohol consumption and smoking status and health care costs (adjusted for age and socio-economic status). Results: Resulting health care costs per person per year amounted to 1290 Euros in 2013, and were 20.1% higher for men than for women. Sex, alcohol consumption, tobacco use and socio-economic status were all associated with health care costs. In particular, alcohol consumption had a positive dose–response association with health care costs. Similarly, both smokers and former smokers had higher health care costs than did people who never smoked. Conclusions: Alcohol and tobacco use had modest and large impacts respectively on health care costs, confirming the results of previous ecological modelling analyses. Reductions of alcohol consumption and smoking through public policies and via early identification and brief interventions would likely be associated with reductions in health care costs.